Development of a FEM waveguide code, incorporating Fast Frequency Techniques, for numerical synthesis - Clarke, Samuel R. (Samuel Robert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2002.